2013
DOI: 10.1017/jfm.2013.454
|View full text |Cite
|
Sign up to set email alerts
|

Thin power-law film flow down an inclined plane: consistent shallow-water models and stability under large-scale perturbations

Abstract: The aim of this paper is to provide a better understanding of the derivation of two moments approximate models of shallow water type for thin power law films down an incline. We limit ourselves to the case of laminar flow for which the boundary layer issued from the interaction of the flow with the bottom surface has an influence all over the transverse direction to the flow. In this case the concept itself of thin film and its relation with long wave asymptotic leads naturally to flow conditions around a unif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 26 publications
(73 reference statements)
2
30
0
Order By: Relevance
“…at vanishing shear-rate) in the power-law shear-thinning constitutive law, in an inverse context, relying on surface velocity observations. As a matter of fact, this singularity might lead to an ill-posed direct problem if a free-surface is considered as pointed out in [16]. For different sliding regimes, sensitivity analysis demonstrate that the refinement of the mesh close to the surface, while leading to the appearance of a stiff (very high viscosity) layer, does not affect the solution and that the viscosity singularity remains passive in the model confirming numerically the analysis done in [17].…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…at vanishing shear-rate) in the power-law shear-thinning constitutive law, in an inverse context, relying on surface velocity observations. As a matter of fact, this singularity might lead to an ill-posed direct problem if a free-surface is considered as pointed out in [16]. For different sliding regimes, sensitivity analysis demonstrate that the refinement of the mesh close to the surface, while leading to the appearance of a stiff (very high viscosity) layer, does not affect the solution and that the viscosity singularity remains passive in the model confirming numerically the analysis done in [17].…”
Section: Introductionsupporting
confidence: 63%
“…But, this law leads to an infinite viscosity singularity for vanishing shear-rates (in the shear-thinning case, n > 1, see equation (6)). In other respect, it has been demonstrated that this singularity might lead to an ill-posed direct problem if a free-surface is considered (see [16]).…”
Section: Issue Addressedmentioning
confidence: 99%
“…Then, using a long-wave approximation, they demonstrated a linear evolution of the critical Reynolds number as a function of both cotγ and the power-law exponent n. This study, however, is limited by the singularity introduced by the viscosity law in the model: a power-law describes an infinite viscosity at the free surface, which is not physically consistent. To remove this singularity, some authors considered a regularized power-law model: Ruyer-Quil et al [5] by introducing a Newtonian plateau at small strain rate and Noble and Vila [6] by introducing a weaker formulation of the Cauchy momentum equations. They have shown the relevant influence of shear-thinning properties on the primary instability.…”
Section: Introductionmentioning
confidence: 99%
“…Lubrication models typically reduce to a single advection-diffusion equation for the evolution of flow height h (Benney 1966;Hunt 1994;Huppert 2006;Ancey, Cochard & Andreini 2009). Shallow-water models are generally formulated as systems of two coupled equations (in two dimensions) for flow height h and discharge q or depth-averaged velocitȳ u = q/h (Savage & Hutter 1989;Ancey et al 2007;Iverson 2013;Noble & Vila 2013), although recently more robust three-equation models, including an additional enstrophy variable, have also been proposed (Richard, Ruyer-Quil & Vila 2016). In these models, fluid rheology is accounted for through closure terms that implicitly depend on the distribution of longitudinal velocity u(y) (with y the cross-stream coordinate) across the flowing layer (Ng & Mei 1994;Ruyer-Quil & Manneville 2000;Hogg & Pritchard 2004).…”
mentioning
confidence: 99%
“…Lubrication models proceed from a leading-order expansion (Benney 1966;Ruyer-Quil & Manneville 1998). At the next level of approximation, derivation of consistent shallow-water models requires expansion of the velocity profile u(y) up to at least O( ) terms (Ruyer-Quil & Manneville 2000;Noble & Vila 2013). Yet, most shallow-water models used in practical applications, either for Newtonian of non-Newtonian fluids, are based on simpler, ad-hoc assumptions.…”
mentioning
confidence: 99%